Analysis of calcium signaling in live human Tongue cell 3D-Cultures upon tastant perfusion. (May 2020) - von Molitor, Elena; Nürnberg, Elina; Ertongur-Fauth, Torsten; Scholz, Paul; Riedel, Katja; Hafner, Mathias; Rudolf, Rüdiger; Cesetti, Tiziana
Graphical abstract: Highlights: Confocal Ca 2+ imaging of live spheroids under acute perfusion enabled by collagen mesh. Spheroids composed of human taste bud-derived cells respond to bitter compounds with Ca2+ signals. Compound-induced Ca 2+ -responses involve ATP-mediated autocrine and paracrine signaling. Regional and single cell analysis reveal stronger and faster Ca 2+ transients of cells on the spheroid periphery. Visualization of Ca 2+ responses upon ATP perfusion up to 100 μm depth in spheroids enabled by light sheet microscopy. Abstract: Bridging the gap between two-dimensional cell cultures and complex in vivo tissues, three-dimensional cell culture models are of increasing interest in the fields of cell biology and pharmacology. However, present challenges hamper live cell imaging of three-dimensional cell cultures. These include (i) the stabilization of these structures under perfusion conditions, (ii) the recording of many z-planes at high spatio-temporal resolution, (iii) and the data analysis that ranges in complexity from whole specimens to single cells. Here, we addressed these issues for the time-lapse analysis of Ca 2+ signaling in spheroids composed of human tongue-derived HTC-8 cells upon perfusion of gustatory substances. Live cell imaging setups for confocal and light sheet microscopy were developed that allow simple and robust spheroid stabilization and high-resolution microscopy with perfusion. Visualization of spheroids made of HTC-8 cells expressing the G-GECO fluorescent Ca 2+ sensor revealed Ca 2+ transients that showed similar kinetics but different amplitudes upon perfusion of bitter compounds Salicine and Saccharin. Dose-dependent responses to Saccharin required extracellular Ca 2+ . From the border towards the center of spheroids, compound-induced Ca 2+ signals were progressively delayed and decreased in amplitude. Stimulation with ATP led to strong Ca 2+ transients that were faster than those evoked by the bitter compounds and blockade of purinergic receptors with Suramin abutted the response to Saccharin, suggesting that ATP mediates a positive autocrine and paracrine feedback. Imaging of ATP-induced Ca 2+ transients with light sheet microscopy allowed acquisition over a z-depth of 100 μm without losing spatial and temporal resolution. In summary, the presented approaches permit the study of fast cellular signaling in three-dimensional cultures upon compound perfusion.